THE WORLDVIEW FOUNDATIONS OF AZERBAIJANI COSMOGONIC AND ETHNOGONIC MYTHS - Kyzylgul Ya. Abbasova (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The relevance of this research is determined by the significance of questions concerning the development of human worldview through the assimilation of cosmogonic and ethnogonic myths, which represent conceptions of the surrounding world. This study aims to investigate the worldview foundations of Azerbaijani cosmogonic and ethnogonic myths, as well as to conduct a philosophical and aesthetic analysis of mythological poetic aspects. Achieving the stated goal involves the utilization of culturalhistorical, philosophical-aesthetic, and mythopoetic research methods. Azerbaijani cosmogonic and ethnogonic myths offer insights into the primordial origins of the world, life on Earth, and the fundamental principles governing the relationship between human communities and nature. They shape the worldviews of individuals, and although they may appear fantastical to contemporary observers, they are pragmatic in guiding how one should comprehend and perceive the surrounding world, assess it, and adapt to it. The timeless truths in the minds of ancient people manifest as a portrayal of the starry sky, with the sun, moon, and stars, elucidating their influence on social life and the relationships between natural phenomena and events. Explanations for the behavior of natural entities have a pragmatic nature, as the understanding of cause-and-effect relationships is projected onto human life, the system of governance, and spiritual-moral values. The philosophical and aesthetic specificity of Azerbaijani cosmogonic and ethnogonic myths is characterized by an anthropocentric and theocentric orientation, in the sense that God or humanity emerges as the core of the mythological worldview and mythological narrative. The inherent anthropomorphism of the natural world, reflecting a primal syncretism, organizes mythological storytelling in which the hero of the myth can be a human, a deity, or an animated natural element. However, semantically, the primary focus of the narrative is not the hero but rather the action or deed. Like myths in other cultures, Azerbaijani myths incorporate ethical elements, featuring evaluative components. However, the subject of evaluation is not the hero but rather the action, process, or deed – precisely these elements serve as the semantic dominants in the description of cosmogenesis and ethnogenesis. The composition of Azerbaijani myths is characterized by specific elements including repetitions, syntactic and figurative parallelism, implicit and explicit comparisons, popular motifs such as the abduction of the Sun and Moon, worldwide floods, themes of death and immortality, light and darkness, and the portrayal of giants carrying the weight of the world, among others. The narrative structure is constructed upon binary oppositions that correspond to the spatial and sensory orientation of human beings, reflecting relationships within a cosmic, social, or sacred continuum. The plots of myths related to the creation of the world are distinguished by variations in their beginnings and event sequences. However, in contrast to European myths, a consistent element in mythological events is the concept of monotheism, which serves as a constant thematic thread throughout these narratives.